The assault on reason - Gore, Albert, 1948- (Penguin Press, 2007)
An analysis of how the politics of fear, secrecy, cronyism, and blind faith has created an environment dangerously hostile to reason. We live in an age when the 30-second television spot is the most powerful force shaping the electorate's thinking, and America is in the hands of an administration less interested than any previous administration in sharing the truth with the citizenry. Of even greater concern is this administration's disinterest in the process by which the truth is ascertained--an open inquiry in which unexpected and even inconvenient facts can lead to unexpected conclusions. Never has there been a worse time for us to lose the capacity to face the reality of our long-term challenges. Gore aims to make us more aware of the forces at work on our own minds, and to lead us to an understanding of what we can do to safeguard our future.--From publisher description.